ANALISIS KETERSEDIAAN AIR DI SUB DAS BATU LAYAR MELALUI PEMODELAN SWAT - Sri Rahayu Ayuba; Noval Ariefrohman Budiprabowo (Jurnal Azimut, 2019)
Batulayar is one of the small watersheds contained in the Limboto / Large watersheds. Where the Limboto watershed as a whole is in the category of drought prone (Ayuba dkk, 2018). The aim of this study; know the availability of the Batu Layar Watershed through SWAT modeling. The method used in this study is the Soil and Water Assessment Tool (wateryield parameter / WYLD) to obtain water availability data. Based on the results of the SWAT analysis, Sub Basin 45 has the largest WYLD value of 626.5 mm, which is administratively located in Molanihu Village. While Sub Basin 32 is a sub basin with the smallest WYLD value of 421.5 mm and administratively this sub basin is located in Pangadaa Village. The value of water which is the result of the accumulation of surface, lateral, and base flow where these three flow patterns determine further planning related to handling the problem of water availability. This indicates that Pangadaa Village has a deficit in water availability when compared to other villages. This needs to be controlled for the conversion of land functions considering that this area is used as dry land agriculture by the community which can result in the threat of water management in this sub basin.